Association between MASP-2 gene polymorphism and risk of infection diseases: A meta-analysis. (November 2016) - Fu, Jie; Wang, Jingqiu; Luo, Yanping; Zhang, Lifeng; Zhang, Yuan; Dong, Xinfang; Yu, Hongjuan; Cao, Mingqiang; Ma, Xingming
Abstract: Background: The role of MASP-2 is vital in the process of complement activation by the lectin pathway. It is generally considered that the functional activation of MASP-2 contribute to the infection disease development process. Aims: To analyze the association between MASP-2 functional gene (rs72550870) polymorphism and the infection disease risk by a meta-analysis. Method: Relevant case-control studies were identiﬁed by searching Cochrane Library, PubMed, Emabase, DOAJ, CAB Abstracts, CSA, CINAHL, EBSCO, Scopus, Global Health, Index Copernicus, CA, China National Knowledge Infrastructure (CNKI) databases up to 10th January 2016. The data were extracted and the methodological quality of studies were evaluated. The STATA 12.0 software was used to perform statistical analysis. Results: 9 studies were included. There was no significant association between masp-2 gene (p.D120G, rs72550870) polymorphism and the risk of infection disease under the allele model (G vs. A: OR = 0.89, 95%CI = 0.66–1.21)( P = 0.445>0.05) and the recessive model (AG + GG vs.AA: OR = 0.88, 95%CI = 0.65–1.20) ( P = 0.428>0.05). Conclusion: This is the first comprehensive meta-analysis indicates that the MASP-2 functional gene (rs72550870) polymorphism is not associated with the infection diseases, and the key functional gene polymorphism of rs72550870 did not increase susceptibility to the infection diseases. Similarly, there were no obvious difference in subgroup analysis based on geographical areas and pathogenic microorganisms. Highlights: The MASP-2 functional gene (rs72550870) polymorphism is not associated with the infection diseases. The key functional gene polymorphism of rs72550870 did not increase susceptibility to the infection diseases. There were no obvious difference in subgroup analysis based on geographical areas and pathogenic microorganisms.